Dynamics of human embryo development in two types of blastocyst media - Kovačič, Borut (Zdravniški vestnik, 2011)
Background: There is a lack of clinical trials on the success of embryo culture in different commercial culture systems in the programme of in vitro fertilization (IVF). In our prospective study, embryo development was compared in two sequential media. Methods: The oocytes from each of 62 patients, treated by IVF/ICSI, were distributed into two groups for 5-day culture in the BlastAssistr System (Medicult, Denmark) (Group 1, n = 421) and in the GIII SeriesTM (Vitrolife, Sweden) (Group 2, n = 415) media. The dynamics of embryo development, implantation and pregnancy rates were compared between groups. Results: The differences between Groups 1 and 2 were first noted on day 3 when GIII yielded more fast-cleaving (> 6 cells) nonfragmented embryos (31.3 % vs. 44.4 %, P < 0.01). On day 4 however, a larger number of compact embryos was found in Group 1 (42.2 % vs. 28.7 %, P <0.005). The percentage of blastocysts or compact morulae on day 5 was the same in both groups (59.6 % vs. 55.6 %). But expanded blastocysts of optimal quality with oval inner-cell-mass developed more frequently in Group 1 (29.2 % vs. 17.7 %, P < 0.05), and therefore more transfers were performed exclusively with Group 1 embryos (28 vs. 17). Pregnancy and implantation rates were the same in both groups (53.6 % vs. 52.9 % and 34.7 % vs. 34.2 %,respectively). Conclusions: Although the GIII SeriesTM yields more fast-cleaving embryos on day 3, embryo compaction (morula) and cavitation (blastocoel) start earlier in the BlastAssistr System media. BlastAssistr System therefore allows easier selection of embryos for transfer on day 5.
Keywords: amplantacija; blastocista; embryo; fertilization; gojišča; morfologija; oploditev; oploditev z biomedicinsko pomočjo; zarodek